COMPARISONS WITH BIRD AND INSECT COMPONENTS IN THE WORKS OF UZBEK WRITERS - Sodiqova S.T, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article is devoted to the study of the stable comparisons with bird and insect components in the works of Uzbek writer A.Kahhar.